Incidental Venous Malformations of the Mandible with Bone Erosion: Successful Treatment with Sclerotherapy, a Case Series. Issue 1 (March 2022) - Marley, Samantha; Harrison, Joshua; Shahriari, Shawhin; Fabre, Anna; Sorte, Danielle; Shetty, Anil; Rogol, Elizaveta
Intraosseous venous malformations are rare lesions in the facial bones often presenting incidentally on imaging, and accounting for 0.5% to 1% of all osseous tumors. Physicians are presented with a diagnostic challenge of differentiating intraosseous venous malformations from bony lesions of the mandible and midface. This is due to the rarity of venous malformations, which often have an asymptomatic course, and the potential for significant intraoperative blood loss. We report 2 cases of asymptomatic facial venous malformations with bone involvement, incidentally, discovered through routine dental radiographic imaging. After evaluation, sclerotherapy was the selected treatment modality for both patients with complete involution. To date, no recurrence of the lesions has been reported.